HUBUNGAN PERILAKU CARING PERAWAT DENGAN KEPUASAN PASIEN DI RUMAH SAKIT BALADHIKA HUSADA JEMBER - Hendyca Putra, Dony Setiawan; Prasetyo, Hendro; Putri, Prestasianita (Politeknik Unggulan Kalimantan, 2023)
Patient satisfaction is an important parameter, based on hospital standards that satisfaction is a form of service quality. Some patients are still dissatisfied with the service received. Patient dissatisfaction is caused by the nurse's lack of caring behavior. The purpose of this study was to the determine the relationship beetweem nurse caring behavior and patient satisfaction at Baladhika Husada Jember Hospital. This study used a correlational design with a cross sectional approach.The population this study were patients treated in the Mawar, Flamboyan and Nusa indah rooms for 2 weeks, namely150 pastients and a sample of 109 respondents was obtained. The sample of this research used Non Probabilty with accidental sampling technique. Data processed to use analyse of univariate and bivariate. Statistic test used Spearmank rank. The results of the nurse's caring behavior research were said to be good at 83.5%, sufficient 11% and less by 5.5% while for patient satisfaction who felt satisfied 86.2% and dissatisfied by 13.8%. At statistical test of Spearmank rank test obtained of p value = 0,000 with α value 0,05. These results indicated that there was a relationship between nurse caring behavior and patient satisfaction at Baladhika Husada Jember Hospital.